The Role of Library Councils in Canadian Higher Education: An Exploratory Study - Revitt, Eva; Luyk, Sean (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
Scholarship exploring the makeup, function, and efficacy of collegial governance structures within the context of Canadian higher education is limited and primarily focused on the board or the senate. This paper expands that scholarship by focusing on the governance structures of the university library. The objective of this study was to determine the extent of library councils in Canadian universities and to examine their composition, role, and function as evidenced in their governing documents. Using Karl Mannheim’s document method to analyze the terms of reference of 23 library councils, findings reveal that, overwhelmingly, library councils function as information-sharing and discussion forums rather than decision-making bodies. The paper concludes with a review of progressive language and governance practice as gathered from the document analysis.